TANGGUNG JAWAB PERAWAT GIGI TERHADAP TINDAKAN PELAYANAN KESEHATAN GIGI YANG SESUAI DAN TIDAK SESUAI KOMPETENSI - Prasko Prasko; Salikun Salikun; Iman Supardan (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe dental nurse responsible to appropriate and incompetent dental servicesABSTRACTAuthority possessed by a dental nurse to perform ministerial duties is the legal authority (rechtsbevoegheid). On the basis of this authority, a health worker is entitled to treatment in accordance with their competence. When the administrative requirements to carry out the profession have been met, then the dental nurse as a profession carrier has obtained the professional authority in the work. However, if a health worker do the job without authority, may be considered to violate one of the professional standards of health workers. The purpose of this study was to determine the responsibility of Dental Nurses implementation of the actions of dental health services in Bergas PHC, Duren PHC and Suruh PHC in district of Semarang. This research is a descriptive study that aims to describe systematically and accurately the facts and characteristics of the population or about a particular field. This study sought to describe a situation or event. The instrument used was the questionnaire.From the results of the study conducted by researchers in the field of the Dental Nurses at Duren PHC, Duren PHC and Suruh PHC in district of Semarang by interview can be seen and showed that the majority of Dental Nurses who work in clinics have been carrying out job responsibilities properly in accordance with the competence of Nurses teeth and is in conformity with the laws and regulations governing dental Nurses. But also the results obtained that a small portion Dental Nurses who perform actions beyond the competence stipulated in the legislation governing the dental nurse. Keywords : Responsibilities of Dental Nurses, Dental Health Care Measures